Exploring the anticancer potential of scopoletin against HER-2 positive breast cancer: an in silico molecular docking study - Adhyaksa, I Nyoman Mahesa Praba; Silawarti, Putu Ayu Karunia; Putra, Made Ferdio Amarta; Laksmiani, Ni Putu Linda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Cancer, defined by the unchecked growth and invasive potential of abnormal cells, remains a global health challenge. Within this context, scopoletin, a compound isolated from the leaves of Impatiens balsamina L., has garnered attention for its potential as an anti-breast cancer agent. This study employed in silico molecular docking techniques to explore scopoletin's interaction with the HER-2 protein, a known target in breast cancer therapy. The docking analysis revealed that scopoletin exhibits affinity towards the HER-2 protein, with a binding energy of -6.3 kcal/mol. Notably, the binding energy of scopoletin is comparable to that of gefitinib, an established cancer drug, further underscoring its potential therapeutic value.